The Influence of Orientation 25 Basic Cadre Skills on the Implementation of Posyandu with the Integration of Primary Services (ILP) - Hasibuan, Henni Sari Dewi (PROMOTOR, 2025)
This study aims to evaluate the impact of the 25 Basic Kader Orientation on the implementation of Posyandu with the Integration of Primary Health Services (ILP). The 25 Basic Kader Orientation is expected to improve the skills of Posyandu cadres in managing Posyandu and providing comprehensive health services across all age groups. Using a quantitative approach, data was collected through observations and interviews with 30 Posyandu cadres from various Posyandu centers in area kelurahan sukapuara. The results of the study showed that most cadres showed significant improvement in their skills in Posyandu management as well as in health services for infants, toddlers, pregnant women, and adults. However, there were challenges related to the lack of skills in providing services for adult and elderly groups, which is a key focus in the implementation of ILP. Implementation evaluation revealed variations in skills among cadres, with some successfully integrating primary health services while others still require improvement. Therefore, there is a need for ongoing efforts to strengthen cadre training comprehensively to improve the quality of public health services optimally.